The Effect of Social-Emotional Competency on Child Development in Western China - Wang, Yehui; Yang, Zhaoxi; Zhang, Yingbin; Wang, Faming; Liu, Tour; Xin, Tao (Frontiers in Psychology, 2019)
This study aimed at investigating the effects of social-emotional competency on pupils’ academic achievement, academic emotions and attitudes, and interpersonal relationships. Participants were 7106 grade four and five students in western China. The results were: (1) Social-emotional competency positively predicted pupils’ academic achievement (including reading, mathematics, and science). (2) Social-emotional competency predicted pupils’ academic emotions and attitudes, which included learning anxiety and learning interest, and academic emotions and attitudes played a mediating role in the relation between social-emotional competency and academic achievement. (3) Social-emotional competency positively predicted pupils’ interpersonal relationships, including peer relationships and teacher-student relationships, and interpersonal relationships played a mediating role in the relations between social-emotional competency and academic achievement. These findings highlighted the importance of social-emotional competency to child development in western China, where many children might lack their parents’ company.